2018
DOI: 10.1177/1524838018757748
|View full text |Cite
|
Sign up to set email alerts
|

Finding Keys: A Systematic Review of Barriers and Facilitators for Refugee Children’s Disclosure of Their Life Stories

Abstract: The systematic review presented in this article aims to reveal what supports and hampers refugee children in telling their, often traumatic, life stories. This is important to ensure that migration decisions are based on reliable information about the children's needs for protection. A systematic review was conducted in academic journals, collecting all available scientific knowledge about the disclosure of life stories by refugee minors in the context of social work, guardianship, foster care, asylum procedur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 75 publications
1
19
0
1
Order By: Relevance
“…The challenges anticipated include recruitment, a high level of attrition, poor literacy among participants and assessment across the wide age range of the study. Recruitment is a particular concern as refugee children and adolescents report feelings of mistrust and self-protection when in a setting that requires self-disclosure, 55 such as mental health interventions like TRT, which is likely to affect intervention and trial participation. However, the trial has been designed to mitigate these challenges where possible (eg, over-recruitment; retention strategies; in-person data collection) and will be instrumental in building the Swedish evidence base for refugee child mental health interventions.…”
Section: Discussionmentioning
confidence: 99%
“…The challenges anticipated include recruitment, a high level of attrition, poor literacy among participants and assessment across the wide age range of the study. Recruitment is a particular concern as refugee children and adolescents report feelings of mistrust and self-protection when in a setting that requires self-disclosure, 55 such as mental health interventions like TRT, which is likely to affect intervention and trial participation. However, the trial has been designed to mitigate these challenges where possible (eg, over-recruitment; retention strategies; in-person data collection) and will be instrumental in building the Swedish evidence base for refugee child mental health interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Nondisclosure of psychosocial stressors and traumatic experiences in undocumented immigrant families is a real and major concern. 1,2 The genesis of nondisclosure of trauma in this population is multifactorial. Undocumented immigrants are less likely to engage with health care and other services for their children.…”
Section: Disclosure In Undocumented Immigrant Familiesmentioning
confidence: 99%
“…5,6 Fear of being treated in a substandard manner because of the presence of mental illness along with preexisting fears of discriminations because of their immigrant status have been identified as some of the factors impacting trust in treatment relationships. 2,4,5 Sandhu et al 5 further identified additional deterrents, including fear of increased vulnerability resulting from divulging sensitive information to clinicians and the possibility that translators may share this information with their community. The risks of legal ramifications and safety are also strong deterrents for trauma disclosure, and some undocumented immigrants fear disclosure of their status to legal authorities by mental health professionals.…”
Section: Disclosure In Undocumented Immigrant Familiesmentioning
confidence: 99%
“…In addition, it can be difficult for professionals to assess these emotional symptoms with the children (Bean et al, 2007;Vervliet et al, 2014). Professionalssuch as guardians, caregivers and social workersneed to take time to build trust and establish a bond (Van Os, Zijlstra, Post, Knorth, & Kalverboer, 2018). Without that, they cannot be expected to see or hear, let alone understand, all the mental health problems that unaccompanied refugee children may experience (Adams, 2009;Chase, 2010;Katsounari, 2014;Kohli, 2006).…”
Section: Implications For Practice and Researchmentioning
confidence: 99%